Influence of vowel harmony in implicit learning of structure phoneme sequences in Croatian and Hungarian - Gnjatović, Tena (Array, 2011)
Vowel harmony is cross-linguistically a well- attested phenomenon that constrains possible occurence of appearance of vowels in a word depending on their quality. Since the possible occurrence of vowels is limited to a certain set, vowel harmony produces a certain level of redundancy. The aim of this research is to see whether vowel harmony facilitates the implicit learning of structured sequences containing both vowels and consonants. The experiment will be conducted on a group of native Croatian and Hungarian speakers, whose task will be to evaluate grammaticality of structured phoneme sequences. The participants will be instructed to base their grammaticality judgment on a set of structured sequences given previously during the training phase, in which all the stimuli are constructed respecting the front-back vowel harmony. In the test phase half of the sequences will observe the front-back harmony pattern. The success of implicit learning will be evaluated on the basis of the percentage of correct responses and on reaction time. The hypothesis is that vowel harmony, due to its increased regularity effect, facilitates implicit learning. Also, more prominent influence of vowel harmony is expected in the native Hungarian group, due to their exposure to vowel harmony from the beginning of language learning.